2018
DOI: 10.1371/journal.pone.0200290
|View full text |Cite
|
Sign up to set email alerts
|

A potential biomarker hsa-miR-200a-5p distinguishing between benign thyroid tumors with papillary hyperplasia and papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common endocrine cancer with a significantly increase of the incidence recently. Several cytokines, such as thyroid peroxidase (TPO), cluster of differentiation 56 (CD56), Galectin-3, mesothelial cell (MC), cytokeratin 19 (CK19) and BRAF (B-raf) were recommended to be tested by immunohistochemistry (IHC) for a definitive diagnosis, but were still limited in clinical use because of their relative lower sensitivity and specificity. MicroRNA (miRNA), as a new molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…A number of studies have reported that intricate biological processes participating in the interactions between polygenes may contribute to the occurrence and progression of TC ( 10 – 12 ). Previous studies have suggested that hsa-miR-200a-5p and hsa-miR-181a-2-3p could be applied for latent diagnostic and prognostic biomarkers of TC ( 13 , 14 ). Nevertheless, the clinical characteristics of molecular profiles in TC have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that intricate biological processes participating in the interactions between polygenes may contribute to the occurrence and progression of TC ( 10 – 12 ). Previous studies have suggested that hsa-miR-200a-5p and hsa-miR-181a-2-3p could be applied for latent diagnostic and prognostic biomarkers of TC ( 13 , 14 ). Nevertheless, the clinical characteristics of molecular profiles in TC have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-200a, as a target of the enhancer, was highly relevant to the survival of thyroid cancer patients ( Figure 5B ). A previous study has shown that miR-200a regulates the epithelial stromal transformation of thyroid cancer through the EGF/EGFR signal ( Xue et al, 2015 ), and it is a key factor in the epithelial phenotype and a tumor suppressor in THCA ( Wang et al, 2018 ). Additionally, the survival analysis showed that patients with low expression of miR-200a have a lower survival time.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Moreover, miR-200a-5p overexpression has recently been described in non-small cell lung cancer (NSCLC), 44 ovarian cancer, 45 breast cancer 46 and papillary thyroid carcinoma, but so far not linked to HLA-I and APM component expression. 47 Alterations in the surface expression and/or function of the HLA-I antigens are frequently found in human tumors and equip neoplastic cells with mechanisms to escape immune surveillance. 5 Furthermore, tumors with acquired resistance to checkpoint inhibitor therapy or adoptive T cell transfer can acquire genetic deficiencies or downregulation of APM components resulting in the loss or reduced expression of either constitutive or HLA-I surface antigens.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 Moreover, miR-200a-5p overexpression has recently been described in non-small cell lung cancer (NSCLC), 44 ovarian cancer, 45 breast cancer 46 and papillary thyroid carcinoma, but so far not linked to HLA-I and APM component expression. 47 …”
Section: Discussionmentioning
confidence: 99%